2009
DOI: 10.1007/s10886-009-9708-3
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles from a Mite-Infested Spruce Clone and Their Effects on Pine Weevil Behavior

Abstract: Induced responses by Norway spruce (Picea abies) seedlings to feeding damage by two mite species were studied by analyzing the volatiles emitted during infestation. Four specimens of a Norway spruce (Picea abies L.) clone were infested with mites of Nalepella sp., another four with Oligonychus ununguis, and four were kept mite-free as controls. After a year of infestation, spruce volatiles were collected, analyzed, and identified using SPME-GC-MS. In addition, enantiomers of chiral limonene and linalool were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 57 publications
0
26
2
Order By: Relevance
“…Several other reports point to similar correlations between SQT (in particular β-farnesene) and oxygenated MTs such as linalool emissions and biotic stresses in controlled experiments. For example, increases in farnesene, methyl salicylate (MeSA), and linalool emissions were reported to be an induced response by Norway spruce seedlings to feeding damage by mite species (Kännaste et al, 2009), indicating that their biosynthesis might prevent the trees from being damaged. Interestingly, the release of β-farnesene seemed to be mite specific and attractive to pine weevils, whereas linalool and MeSA were deterrents.…”
Section: Variability Of the Voc Emissionsmentioning
confidence: 99%
“…Several other reports point to similar correlations between SQT (in particular β-farnesene) and oxygenated MTs such as linalool emissions and biotic stresses in controlled experiments. For example, increases in farnesene, methyl salicylate (MeSA), and linalool emissions were reported to be an induced response by Norway spruce seedlings to feeding damage by mite species (Kännaste et al, 2009), indicating that their biosynthesis might prevent the trees from being damaged. Interestingly, the release of β-farnesene seemed to be mite specific and attractive to pine weevils, whereas linalool and MeSA were deterrents.…”
Section: Variability Of the Voc Emissionsmentioning
confidence: 99%
“…Direct defenses act directly against the herbivores, whereas indirect plant defenses may act by release of plant volatile organic compounds (VOCs) that attract natural enemies of the herbivores (see for reviews Gershenzon and Dudareva, 2007;Poelman et al, 2008;Dicke, 2009). Quantitative and qualitative herbivoreinduced changes in VOC emissions have attracted special attention (Holopainen, 2004;Arimura et al, 2005;Dicke, 2009;Kännaste et al, 2009;Wu and Baldwin, 2009;Schaub et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Benzaldehyde, benzyl alcohol, and limonene released by apple trees both before (this study) and after bloom [1] were found to be attractive for the plum curculio Conotrachelus nenuphar (Herbst) when tested singly in the field [21] [22]. Methyl salicylate emitted from the Norway spruce had a deterrent effect on the pine weevil Hylobius abietis (L.) in combination with otherwise attractive spruce odor [12]. It cannot be excluded that methyl salicylate and/or any other compounds, detected in the apple headspace in the present work, can be deterrent for A. pomorum when separated.…”
mentioning
confidence: 59%
“…The weevil most likely also relies on olfactory cues to locate its host plant and to discriminate among cultivars [9], but direct evidence for the attraction of the weevil to apple volatiles is lacking yet [10]. In other curculionids, recent studies substantially contributed to the knowledge on volatile cues in host detection [11] [12], stimulating the present investigation of the volatiles emitted from apple at the beginning of the growing season as well as their relevance in host location of A. pomorum. Volatiles emitted at three consecutive phenological stages covering the period of orchard colonization by the weevil were identified, and subsequently, the effect of a recombined synthetic blend on weevil behavior was studied.…”
mentioning
confidence: 99%